(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Ecotourism is one strategy for supporting conservation, generating income, and creating employment for communities living around protected areas. In Malaysia, the management of national parks (protected areas) focuses on the planning and implementation of various activities which contribute to the long-term conservation of the areas while mitigating or reducing conflicts between human and the environment. The issue is whether ecotourism development helps to improve income and reduce rural poverty. A case study was conducted in 2014 where 158 Malay households from Kampung Kuala Tahan were interviewed. Villagers engaged in economic activities related to ecotourism development in Kuala Tahan National Park (KTNP) area (2,477 sq. km) directly and indirectly. The result shows the average monthly household income of this village was RM4, 035. On the whole, about 90% of the average monthly household income was cash income while 10% income in kind. The income sources of villagers were from those within the state land forest areas (related to NTFP harvesting), and outside KTNP (related to forestry and ecotourism). Income generated outside KTNP (related to forestry and ecotourism) area was significantly high compared to those within state land forest and outside KTNP (non-forestry). On average, about RM1, 895 or 47% of the average monthly household income was generated from the ecotourism related activities and forest area. The highest percentage of cash income was from villagers’ engagement as tour guides. Income generated from this source accounted for 13% of household income. Ecotourism related retail stores or restaurant operators also significantly contributed to the average monthly household income at 10%. The incidence of poverty among the households in the village was 4% in 2014 compared to 3.4% among rural Malaysian households in 2012. The findings in this study showed that the income received from forestry related activities and ecotourism is important in reducing poverty among local households.